PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN HAND AND BODY LOTION VASELINEDI KOTA SEMARANG - Puja Ratna Sari (Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this research is to analyze the influence of product quality, price perception and electronic word of mouth on purchasing decisions. This research was conducted using quantitative metodhs. The population in the study involved Vaseline hand and body lotion in Semarang City, with a sample of 96 respondent selected using a purposive sampling technique. The data analyzed is primary data collected using a questionnaire. Based on the results of the SPSS version 26 test, the results of the research instrument showed the all indicators were declared valid and all variables were declared reliable. The results of the t test and regression coefficient show that the product quality variable has a positive and significant effect on decisions, electronic word of mouth has a positive and significant effect on purchasing decisions, while price perception does not have a significant effect on purchasing decisions. Based on the model test results, the three independent variables were able to explain 64.3 percent of the dependent variable.